The variability and predictability of summer southwest monsoon intensity measurement index across mainland indochina: from local synoptic to large scale perspectives - Kyaw Than Oo; Yinshuo Dong; Kazora Jonah (Environmental Research Communications)
The mainland Indochina Southwest Monsoon (MSwM) is a crucial climatic phenomenon in Southeast Asia, significantly influencing the climate of countries such as Myanmar, Bangladesh, Thailand, Laos, and Southwest China. Traditionally, the intensity of the MSwM has been challenging to quantify due to its complex nature. This study introduces a new Southwest Monsoon Intensity Index (SMII), based on sea level pressure (SLP), which offers a more comprehensive understanding of the monsoon’s intraseasonal to interannual variability and its associated climate anomalies. The SMII is designed to overtake the limitations of local indices, which often rely on data from only two costal stations and may lack the resolution necessary for seasonal outlooks or long-term forecast modeling. By considering both south-north and west-east annual dominant pressure field gradients, the SMII provides a more robust measure of monsoon intensity. This large-scale index is influenced by key pressure systems, such as the Tibet Low and the Mascarenes High, and is characterized by the movement of a concentrated north-south rain belt and a quasi-stationary low-level jet. Our analysis reveals strong correlations between the SMII and regional rainfall patterns, particularly during the peak intensity of the summer months. Additionally, significant associations with El Niño Southern Oscillation (ENSO) indices and the eastern Indian Ocean suggest potential teleconnections, which can enhance predictive capabilities. This improved index is crucial for operational climate centers to monitor and predict monsoon behavior effectively, ultimately aiding in the forecasting and managing the MSwM’s socio-economic impacts.